The Naqli and 'Aqli Integration in the Teachings of Community Health Posting - Dzulkhairi, MR; Zairina, AR; Nooriah, MS; Yunus, M (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by SCOPUS/WOS